Personality Styles of Dentists Practicing Hypnosis Confirm the Existence of the Homo Hypnoticus - Wolf, Thomas Gerhard; Baumgärtner, Elena; Peter, Burkhard (Frontiers in Psychology, 2022)
Several publications with health care professionals such as psychotherapists have shown a significant difference in personality styles in practitioners using hypnosis compared to those not using hypnosis. In order to investigate differences in personality styles, dentists were contacted to participate in a personality-inventory-(PSDI)-online -survey. Hypnosis using dentists (HYP DGZH) (n=418) were compared to dentists not using hypnosis (NONHYP DENT) (n=162). Results show that hypnosis practicing dentists score significantly higher in the intuitive/schizotypal ST personality style (p<.001) compared to non-hypnosis practicing dentists. Female dentists scored significantly higher on intuitive/schizotypal ST and unselfish/self-sacrificing SL in the HYP DGZH sample, but only on unselfish/self-sacrificing SL in the NONHYP DENT sample. The percentage of women was similar in both samples (68.2%; 67.3%). Intuitive/schizotypal ST was found to be the predominant personality style of men who are interested in or use hypnosis, metaphorically so-called "homo hypnoticus". Within the limitations of this cross-sectional non-interventional observational online-questionnaire study, results expand this notion to a so-called “homo hypnoticus dentalis”. However, further research on the subject is needed to investigate and confirm this personality type in other than the German speaking DACH-countries.